New Occurrences of Macrofungi (Basidiomycota) in Southern Amazonas, Brazil - Cavalcante, Felipe Sant’Anna; Campos, Milton César Costa; Lima, Janaína Paolucci Sales de (Ciência e Natura, 2022)
Macrofungi are organisms that have macroscopic reproductive structures, called ascocarps and basidiocarps, and are important representatives of Ascomycota and Basidiomycota, respectively. The Amazon rainforest, as it offers a large number of natural resources, is one of the biomes that has been under great environmental pressure and sustainable use that takes into account social, economic and ecological factors is extremely important for protecting the forest. Given this context, this work aimed to present the characterization of the species that constitute occurrences of macrofungi for the Southern region of the state of Amazonas, contributing to the expansion of the knowledge on the geographical distribution of the specimens found. This survey was carried out at the Tenente Pimenta Jungle Base located 20 kilometers from the Municipality of Humaitá- state of Amazonas. The collections were carried out in two different periods, in the pre-existing trails of the Tenente Pimenta Jungle Base (54th BIS). 115 specimens belonging to 11 families were found, with species belonging to Ascomycota and Basidiomycota being identified. The data related to the collection periods of macroscopic fungi were from August 2019 and November 2019. In August 2019, a dry season in the Amazon, with little rain, 70 specimens of macrofungi were collected. In November, a rainy period in the Amazon, 105 specimens of macrofungi were collected. The data obtained from this research will serve as a basis for further studies in the state of Amazonas, since it is a pioneer in the southern region of the state. There is a great diversity of macrofungi in the study area, however, edaphoclimatic factors are relevant at different periods of the year.